S.M.O Solution: An Innovative Design Approach to Optimize the Output of BIPV Systems Located in Dense Urban Environments. (June 2016) - Frontini, Francesco; Bouziri, Salim M.; Corbellini, Gianluca; Medici, Vasco
Abstract: BIPV technologies applied to façades are strongly affected by complex and dynamic shadings especially when located in dense urban environments. In this case, the shading effects need to be evaluated in detail in order to properly estimate the energy yield and optimise the energy harvest of such PV systems. The S.M.O (String Matching Optimisation) solution represents a new approach, entirely based on open-source software, which allows a very accurate study of the shading effects on façades and the investigation of electrical behaviour of BIPV strings under complex irradiation patterns. This solution has been validated with a real pilot BIPV façade located in southern Switzerland and the model was simulated on other theoretical PV façades with different levels of complexity. The presented method allows an accurate evaluation and optimisation of the energy yield of BIPV facades in complex urban environments.